Risk factors and survival of patients with permanent pacemaker implantation after heart transplantation - Rivinius, Rasmus; Helmschrott, Matthias; Rahm, Ann-Kathrin; Darche, Fabrice Fernand; Thomas, Dierk; Bruckner, Thomas; Dösch, Andreas; Ehlermann, Philipp; Katus, Hugo; Zitron, Edgar (Journal of thoracic disease, 2019)
Background: Permanent pacemaker (PPM) implantation after heart transplantation (HTX) may be required due to severe bradycardia. The aim of this study was to investigate the risk factors, indications, perioperative outcomes and complications of PPM implantation after HTX as well as the underlying effect on post-transplant mortality including causes of death. - Methods: This registry study included 621 patients receiving HTX at Heidelberg Heart Center between 1989 and 2018. Patients were stratified by PPM implantation after HTX. Data analysis of risk factors for PPM implantation included donor and recipient demographics, post-transplant medication, mortality, and causes of death. - Results: Thirty-six patients (5.8%) received PPM implantation after HTX, 12 (33.3%) with early PPM and 24 (66.7%) with late PPM. Indications for PPM implantation after HTX included sinus node dysfunction (SND) (n=15; 41.7%) and atrioventricular block (AVB) (n=21; 58.3%). Multivariate analysis revealed recipient body mass index (BMI) [hazard ratio (HR): 1.10; confidence interval (CI): 1.01-1.21; P=0.03], donor age (HR: 1.07; CI: 1.03-1.10; P Conclusions: Multivariate risk factors for PPM implantation after HTX include recipient BMI, donor age, and biatrial HTX. Early PPM implantation after HTX is associated with increased 5-year post-transplant mortality due to infection.
Gesehen am 22.01.2020